2020
DOI: 10.1177/0954008320976748
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 25 MeV Si ions and 25 MeV O ions on the chemical and structural properties of PEEK films

Abstract: Poly (ether ether ketone) (PEEK) material can be used in a wide variety of fields, such as the aerospace, automotive, electronics, and nuclear industries. In this research, the irradiation effect of 25 MeV Si ions and 25 MeV O ions on the PEEK films was studied, focusing on the changes in chemical and structural properties. By analyzing surface morphology and microstructure evolution of the PEEK films after 25 MeV Si ion and 25 MeV O ion irradiation, particles were generated on surface of the PEEK after 25 MeV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The in uence of Si and O ions, with 25 MeV energy, on the chemical and structural properties of PEEK lms was investigated in 9 . The results showed that the surface roughness of the PEEK material decreases after irradiation by both Si and O ions.…”
Section: Introductionmentioning
confidence: 99%
“…The in uence of Si and O ions, with 25 MeV energy, on the chemical and structural properties of PEEK lms was investigated in 9 . The results showed that the surface roughness of the PEEK material decreases after irradiation by both Si and O ions.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of Si and O ions, with 25 MeV energy, on the chemical and structural properties of PEEK films was investigated in the work by Yang et al 13 . The results showed that the surface roughness of the PEEK material decreases after irradiation by both Si and O ions.…”
Section: Introductionmentioning
confidence: 99%